Clinical daily rhythms of seizure in different subtypes of temporal lobe epilepsy - Gong, Shuxian; Long, Zhongyuan; Ji, Dongyan; Guo, Qiang; Zhang, Tianpeng; Li, Shaochun; Yang, Xiaofeng; Sui, Lisen (Frontiers in Neurology, 2025)
IntroductionThe relationship between circadian rhythms and seizures in temporal lobe epilepsy (TLE) has been well recognized, but it remains poorly understood how the interaction between the endogenous clock system and seizures may affect seizure patterns and patient management. This study investigates the circadian rhythm patterns of clinical seizures in TLE, with a focus on different subtypes and clinical variables.MethodsWe retrospectively analyzed the seizure rhythms of patients diagnosed with TLE who were admitted to the video-EEG ward. Patients were categorized based on clinical data, including mesial, lateral, mesio-lateral, and temporal pole types, as well as left, right, and bilateral temporal lobe involvement. Seizure onset times, frequency, and duration were recorded for each patient.ResultsOur findings indicate that TLE patients exhibit notable seizure rhythms, with the peak times of seizure frequency and duration differing across subtypes and age groups. Notably, patients with mesial and mesio-lateral temporal lobe epilepsy showed peak seizure durations between 23:00 and 24:00, while seizure frequency peaked between 19:00 and 20:00 for right temporal lobe patients and between 19:00 and 22:00 for left temporal lobe patients. Additionally, children and adults had distinct seizure rhythms, with children peaking between 21:00 and 24:00, while adults had a peak frequency between 19:00 and 22:00.DiscussionThese findings highlight the variability of seizure rhythms in TLE and underscore the need for personalized treatment strategies that consider circadian factors, potentially leading to better seizure management and therapeutic interventions.